Pedogênese e morfogênese na superfície de São José dos Ausentes (RS) no quartenário tardio: evidências em paleofundo de vale na bacia hidrográfica do rio dos Touros - Pereira, Josielle Samara (2017)
A significant number of studies has investigated the surface of Palmas (Paraná state)/Água Doce (Santa Catarina state), in the south of Brazil, aiming at understanding the evolution of its geomorphologic landscape in relation to the phenomena of pedogenesis and morphogenesis and, therefore, contributing with studies of the quaternary. It remains unclear, however, if the recognized phenomena are present on a local or a regional scale. Additionally, few studies have considered the continental quaternary in the Southern state of Rio Grande do Sul. Within this context, the present work attempts to identify the abovementioned scale as well as to contribute to the continental paleoenvironmental reconstruction of the South of Brazil. More specifically, the objective of this study is to recognize the occurrence of pedogenesis and morphogenesis phenomena on the surface of São José dos Ausentes (Rio Grande do Sul state) at the Late Quaternary, based on evidence from stratigraphic records of valley paleodepth of second-order hierarchy, in and attempt to understand the evolutionary picture of the second-order hierarchy valley. The methodological approach involved the use of a set of litho-, pedo-, allo- and chronostratigraphic criteria to characterize the materials from the pedostratigraphic section, as well as fieldwork and laboratory analyses. Thirty (30) stratigraphic horizons were recognized in the studied stratigraphic section, and they were distributed in three colluvial sequences – upper pedogenized; middle; and basal colluvial – and one pedogenetic hydromorphic sequence located at the base of the section. The integration of the results revealed that during the Late Interstadial (> 25,000 years BP), at the valley paleodepth, there were hydromorphic soil and hypodermic water flows on its drainage axis, similar to those found of the surface of Palmas/Água Doce, corresponding to the pedogenesis predominance phase. Afterwards, there was continuous action of the morphogenesis, generated by the alternation between processes of subtle mass-movement and surface runoff. The first morphogenesis events were punctual and responsible, and occurred between the end of the Last Interstadial and the Last Glacial Maximum. During the Last Glacial Maximum, the morphogenesis began to be governed by surface runoff. From >25.000 to >19.150 years BP, the sedimentation of colluvial units generated the pedostratigraphic levels equivalent to the basal colluvial sequence. From 19.150 years BP onwards, the sedimentation lost intensity and erosion predominated, promoting the installation of linear erosive incisions (paleogully) that truncated the basal colluvial sequence and part of the hydromorphic level. Soon after that, the morphogenesis again registers sedimentation governed by surface runoff. As a consequence, the colluvial units related to the intermediate colluvial sequence were generated. This phase lasted from <7.940 to >4.860 years BP, corresponding to the mid-Holocene. After 4.860 years BP, the morphogenesis continued to act, originating the upper colluvial sequence, however it lost vigor by the action of the pedogenesis, thus favoring melanization of the sequence. At this phase, the second order valley paleodepth became completely collimated and remobilized, constituting a morphology similar to the slope slightly inclined to the modern low-order hierarchy axis.